Online Courses - Opportunity offered by Research4Life (Confluenţe Bibliologice, 2018)
In the article are described “AGORA on-line Course: Fundamentals of Information Literacy and Access to Global On-line Research in Agriculture”, organized by the Food and Agriculture Organization of the United Nations, FAO, in Cooperation with RUFORUM (Research4Life). More than 1,500 audiences from around 100 countries participated in the courses, including a librarian from Scientific Library USARB.
Keywords: databases; continuous professional training